Growth and development in gymnastics - Klein Ritchie, L.; Ronshaugen, N.; Sygo, J. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
In order to fully grasp the differences of growth and development in a gymnast, it is crucial to first review normal adolescent growth and development. Puberty is the time in an adolescent`s development marked by rapid skeletal and muscular growth along with the development of secondary sex characteristics and reproductive organs. Rapid brain changes occur, along with psychosocial adjustments. Adolescents also develop increased strength and endurance, a key component for success as a gymnast.